The Correlation between Parenting Styles and School Readiness for Children with Hearing Impairment - Dyah Retno Septiani; Munawir Yusuf (Department of Special Education, 2019)
The readiness of students to start learning is the first important thing in the learning process. Readiness is the overall condition of a person in adjusting with the conditions. It is assumed that readiness is influenced by parenting styles. This research aims to determine the correlation between parenting styles and school readiness for children with hearing impairment. This research used quantitative approach with correlational design. The data were collected using a questionnaire and analyzed using linear regression. The results of this research showed that both simultaneously and partially there is no significant correlation between parenting styles and school readiness for children with hearing impairment.